Prevalence and molecular characterization of hepatitis B virus infection in HIV-infected children in Senegal - Toyé, Rayana Maryse; Diop-Ndiaye, Halimatou; Lô, Gora (Elsevier Masson SAS, 2020)
Background and aims: Sub-Saharan Africa (SSA) is the region with the most patients co-infected with the human immunodeficiency virus (HIV) and the hepatitis B virus (HBV) worldwide. However, few studies have focused on SSA children who are at a higher risk of developing a chronic infection than adults. Furthermore, children on first-line antiretroviral therapy (ART) including low genetic barrier drugs may develop both HBV and HIV resistance mutations. The aim of this work was to document HIV-HBV co-infection and to characterize the HBV isolates in children in Senegal. Methods: This is a retrospective study of 613 children infected with HIV on ART or not. Dried blood spot (DBS) specimens were used to detect hepatitis B surface antigen (HBsAg) with a rapid diagnostic test (RDT). Confirmation of HBsAg status and hepatitis B e antigen (HBeAg) detection was performed on an automated platform using the chemiluminescence assay technology. HBV viral DNA was quantified by real-time polymerase chain reaction (PCR) and the preS1/preS2/HBsAg region was genotyped by nested PCR followed by sequencing using the Sanger technique. Results: The prevalence of HIV-HBV co-infection was 4.1% (25/613). The median age of co-infected children was 13 years (2 years-16 years) and 40% (10/25) were girls. Almost all 19/20 (95%) were infected with HIV-1 and 79% (19/24) were treated with 3TC-based triple combination ART. The median duration of time on ART was 15 months (3 months-80 months). More than half of the children 53% (9/17) were experiencing HIV virologic failure and 75% (6/8) had at least one HIV-related resistance-associated mutation (RAM). Of the six children with resistance, none of the three administered treatments were effective on HIV. Of the 25 co-infected children, 82% (18/22) were HBeAg-positive, while the median HBV viral load (VL) was 6.20 log10 IU/mL (24/25 patients), and 62,5% (10/16) of the children had a persistent HBV viremia. Combination of ART was the only factor associated with HBV viremia persistence. Amplification was successful in 15 out of 16 patients (rate of 94%), and the ensuing phylogenetic analysis revealed that eight strains (53%) belonged to genotype A and seven (47%) to genotype E. HBV-related 3TC RAMs were uncovered in 20% of these patients (3/15). HBsAg escape mutations were found in 20% of the children (3/15). Conclusions: Our results showed a high level of drug resistance mutations to both HIV and HBV, a significant level of HBsAg escape mutations, HBV DNA persistence and HIV virologic failure in co-infected children in Senegal. The HBV genotypes found were A and E.
Keywords: HIV; HBV; Abdoul Magib Cissé; Anna Julienne Selbé Ndiaye; Khady Kébé-Fall; Ahmadu Bello University; CEA-SAMEF; Resistance mutations; Children; Genotypes; Senegal